(untitled) (Global Business Management Review (GBMR), 2022)
Although performance measurement system (PMS) has been implemented in many organizations to improve their performance, somehow the unintended consequences of the system may outweigh its benefits. To paint a better picture of their performance for evaluation purposes, employees may resort to measures manipulation or distortion, gaming, smoothing or budgetary slack, even if it results to sub-optimization, or the decline in the organization’s overall performance. Managers may also become short-term oriented at the expenses of long term profitability. Since ethical work climate is believed to guide the employees’ behavior in an organization, then instilling and managing a strong ethical climate would surely discourage such dysfunctional behaviors. At the same time, would climate also influence the ability of the employees to recognize the moral issues and treated them as ones? On the other hand, how would locus of control interact with ethical climate to affect such dysfunctional behavior in the context of performance measurement system? These issues are certainly interesting and worth further investigation, especially in the period of rising unethical scandals worldwide.